Synoptic, Dynamic Analysis and Numerical Simulations of Extreme Flood Cases in Pieria Region - Dimitrios Bampzelis; Stergios Kartsios; Ioannis Pytharoulis; Vassilios Kostopoulos; Christos Spyrou; Ioannis Tegoulias; Prodromos Zanis (Environmental Sciences Proceedings, 2023)
The synoptic and dynamic characteristics of three extreme precipitation events over the area of Pieria are analyzed. The objective of this study is to identify similarities in structure, intensity and behavior of the synoptic patterns that were responsible for the extreme precipitation over the examined area. Precipitation-derived data from weather radar images were also used to identify the intensity and extent of the events. The high-resolution non-hydrostatic WRF-ARW numerical weather prediction model was also used to simulate these intense precipitation events. Results indicated analogous synoptic conditions in all three cases suggesting the strong synoptic forcing of the events in extreme precipitation over the area. The model was able to capture these events adequately, even though discrepancies occurred regarding the intensity and the location of the precipitation maxima.